EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DAN FAKTOR YANG MEMPENGARUHI NYA DI SEKOLAH MENENGAH PERTAMA NEGERI 2 PALEMBANG - Elvarina elvarina (Conciencia, 2015)
Principal study in this research is how the effectiveness of school leadership and the factors that influence the effectiveness of school leadership in SMPN 2 Palembang? Departing from the background that there are teachers who do not go to class when the bell rings (lack of discipline), the principal less attention to the performance of teachers and staff, did not reprimand the teacher error. Supposedly the principal has six ability namely, the ability to coordinate, conflict resolution ability, the ability to establish communication, the ability to motivate and mobilize the staff, the ability to build staff, and the ability to build a working relationship. This type of research in this thesis is qualitative research is to explain, describe, and outlines then are drawn conclusions about the effectiveness of school leadership and influencing factors in SMP Negeri 2 Palembang with seven informants headmaster deputy head of the curriculum, the deputy head of student affairs, deputy head of facilities and infrastructure, the deputy head of public relations, administrative coordinator and teacher. The data source consists of a source of primary data obtained from the first source that principals, representatives, administrators, and teachers while secondary data sources such as books and school documentation with respect to this research. Data were collected through observation, interviews, and documentation. After the data is collected and examined its validity and validity, then edited, then the data is classified in accordance with aspects of the problem, and then simplified, presented and conclusions drawn and the results obtained. This study uses analysis techniques Miles and Huberman and triangulation so that the problem be viewed from different angles, from different sources, problems, and methods of collecting data. The research results show: First, the effectiveness of school leadership in SMPN 2 Palembang is effective. The effectiveness of school leadership is viewed in terms of the ability of coordination, conflict resolution ability, the ability to establish communication, the ability to mobilize and motivate staff, develop staff capabilities, and the ability to build a working relationship. Second, the factors that influence the effectiveness of school leadership in SMP Negeri 2 Palembang is a friendly personality, wisdom, empathy, courage to face the challenges, and being able to choose the leadership style according to the situation.